PEMANTAUAN PERUBAHAN PERUBAHAN LAHAN HUTAN YANG DILINDUNGI BUKIT SULIGI KABUPATEN KAMPAR PROVINSI RIAU - Mini Silviana; Rudianda Sulaeman; Yossi Oktorini (JURNAL ILMU-ILMU KEHUTANAN, 2019)
Bukit Suligi Protection Forest was a protected forest in Riau area which is a stretch of wet tropical forest. The forest land cover of this area continues to decline due to forest fires and forest area conversion. These problems will affected changes in the Bukit Suligi Protection Forest cover. Efforts to find out the change in cover of Bukit Suligi Protected Forest Area land was monitored to see changes in land cover in the area. The purpose of research was changes detection the Bukit Suligi Protection Forest cover in Kampar District through interpretation of Landsat imageries 1997, 2007 and 2017. Identify factors that cause changes in the cover of Bukit Suligi Protection Forest. This research analyzed land cover changes and interviews. Based on the results of interpretation of Landsat imageries in 1997, 2007 and 2017, land cover changes that occurred in the period 1997 - 2017 reached 4447.62 ha or 76.76% of the total area. If described in the period 1997 - 2007 land cover changes amounted to 2920.32 ha or 50.40% of the total area, these changes continue to increase until the period 2007 - 2017 land cover changes of 3627 ha or 62.60% of the total area. Factors that influence changes in the cover area of Bukit Suligi Protection Forest are natural factors and human factors. The human factor consists of population growth and government policies, namely the lack of supervision by the government in the forestry sector, specifically the management of the Bukit Suligi Protected Forest area.